(3GdQhV GdCQjVs
(3ChdgG (B:s
(3aPGc GSe jWGHbI GdeSei hgPG cfjJg HGHf Jejei jchf dce THjgkG ai GdeYGdi s
(3BNQgG (B:s
(3CWdYc Gddg Ydi cd eG jfMi ef GdeQghH gPg BNQ cdeI bGdgG hcdGeg CcKQ ef gPG hGdMeO ddg Mb MeOg hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3MGdI GdfSNI LjOI s
Keywords: (3GdCOHs